Kerygma/History and the Gospel Genre - Vorster, W. S. (1983)
The thesis I wish to propound in this article is that neither kerygma nor history is a distinctive characteristic of the genre of the gospels. For the literary critic this remark may seem superfluous while a New Testament scholar may find it ridiculous. In view of the history of the interpretation of the genre, however, and also in view of current discussion on the problem in New Testament scholarship the thesis is understandable. The article falls into two parts. In the first a short survey is given of the problem and its development. In the second kerygma and history are discussed with reference to the gospels as narratives.